Dynamic distribution of gut microbiota in cattle at different breeds and health states - Wang, Lei; Wu, Daoyi; Zhang, Yu; Li, Kun; Wang, Mingjin; Ma, Jinping (Frontiers in Microbiology, 2023)
Weining cattle is a precious species with high tolerance to cold, disease, and stress, and accounts for a large proportion of agricultural economic output in Guizhou, China. However, there are gaps in information about the intestinal flora of Weining cattle. In this study, high-throughput sequencing were employed to analyze the intestinal flora of Weining cattle (WN), Angus cattle (An), and diarrheal Angus cattle (DA), and explore the potential bacteria associated with diarrhea. We collected 18 fecal samples from Weining, Guizhou, including Weining cattle, Healthy Angus, and Diarrheal Angus. The results of intestinal microbiota analysis showed there were no significant differences in intestinal flora diversity and richness among groups (p > 0.05). The abundance of beneficial bacteria (Lachnospiraceae, Rikenellaceae, Coprostanoligenes, and Cyanobacteria) in Weining cattle were significantly higher than in Angus cattle (p < 0.05). The potential pathogens including Anaerosporobacter and Campylobacteria were enriched in the DA group. Furthermore, the abundance of Lachnospiraceae was very high in the WN group (p < 0.05), which might explain why Weining cattle are less prone to diarrhea. This is the first report on the intestinal flora of Weining cattle, furthering understanding of the relationship between intestinal flora and health.